KEANEKARAGAMAN JENIS PARASITOID TRICHOGRAMMATIDAE HAMA Helicoverpha armigera BERDASARKAN KARAKTER MORFOLOGI PADA TANAMAN JAGUNG DI SULAWESI UTARA - Maramis, R. T.D.; Kandowangko, D. S. (EUGENIA, 2013)
ABSTRACT   The research was aimed to identify parasitoid, to know the morphology characters to count the level parasitisation of parasitoid, to the region of parasitoid distribution and to make a key parasitoid identification. Sampling eggs of H. armigera in order to get a type of parasitoid Trichogrammatidae has carried out in the regencies of Minahasa, South Minahasa and Bolaang Mongondow. Each regency has sampled in three sub-districts for getting the egg samples of H. armigera, which were collected at the age plant of 45-52 days after planting. Sampling result of egg H. armigera has found one type of parasitoid Trichogrammatidae. Based on the identification of parasitoid morphology, i.e: the front wings, antenna, the insect, colors, parasitoid in which parasited the eggs of H. armigera is Trichogrammatoidea sp.. Body color of parasitoid Trichogrammatoidea sp.. was tawny, and the abdominal was more dark. Parasitoid Trichogrammatoidea sp. spread on the planting sub-districts. Parasitization of parasitoid was still low, only ranging from 5.59 to 21.03 percent, the highest and lowest values found in Bolaang Mongondow (Poigar and Bolaang subdistricts). Keywords : type of parasitoid Trichogrammatidae, parasitisation of  parasitoid   ABSTRAK Penelitian bertujuan mengidentifikasi parasitoid, mengetahui karakter morfologi, menghitung tingkat parasitisasi parasitoid, mengetahui wilayah penyebaran parasitoid dan membuat kunci identifikasi parasitoid. Pengambilan contoh telur H. armigera untuk mendapatkan jenis parasitoid Trichogrammatidae telah dilaksanakan di Kabupaten Minahasa, Minahasa Selatan dan Bolaang Mongondow. Setiap wilayah Kabupaten diambil 3 kecamatan untuk pengambilan contoh telur H. armigera. Contoh telur H. armigera dilaksanakan pada umur tanaman 45-52 hst. Hasil pengambilan contoh telur H. armigera telah ditemukan satu jenis parasitoid Trichogrammatidae. Berdasarkan identifikasi karakter morfologi parasitoid yakni sayap depan, antenna, warna tubuh serangga, maka parasitoid yang memarasit telur H. armigera adalah Trichogrammatoidea sp.. Warna tubuh parasitoid Trichogrammatoidea sp. armigera berwarna kuning kecoklatan dan bagian abdomen berwarna lebih gelap.  Parasitoid Trichogrammatoidea sp. menyebar pada semua pertanaman jagung di ketiga wilayah kabupaten.  Parasitisasi parasitoid masih tergolong rendah hanya berkisar antara 5,59-21,03%, wilayah yang tertinggi dan terendah ditemukan di Bolaang Mongondow (di Kecamatan Poigar dan  Bolaang. Kata kunci : jenis parasitoid Trichogrammatidae, parasitisasi parasitoid